2017
DOI: 10.3390/f8120487
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Net Stocked Plantation Area for Small-Scale Forests in New Zealand Using Integrated RapidEye and LiDAR Sensors

Abstract: Abstract:In New Zealand, approximately 70% of plantation forests are large-scale (over 1000 ha) with accurate resource description. In contrast, the remaining 30% of plantation forests are small-scale (less than 1000 ha). It is forecasted that these small-scale forests will supply nearly 40% of the national wood production in the next decade. However, in-depth description of these forests, especially those under 100 ha, is very limited. This research evaluates the use of remote sensing datasets to map and esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…LiDAR is capable of directly capturing the three-dimension information on forest structure via actively transmitting laser pulses that interact with forest structure and then receiving the return signals. It has evolved into the preeminent remotely sensed platform to characterize detailed information of forest attributes spatially, since the end of the last century [10][11][12][13][14][15][16][17][18] due to its high precision and flexibility critical for operational forest management, and it has been extensively adopted for artificial or natural forest attributes monitoring on the individual tree-level [19][20][21] and small-scale [22][23][24]. Moreover, forest volume, as one of the structure parameters, was often accurately estimated by LiDAR [25], for example, Clementel et al [26] have carried out statistical models combined with medium-resolution LiDAR to produce timber volume mapping, and Lo et al [19] demonstrated tree growth competition index (LCI) derived from LiDAR scanning while using a rasterized canopy height model (multilevel morphological active-contour algorithm) was a key factor for forest volume estimation.…”
Section: Introductionmentioning
confidence: 99%
“…LiDAR is capable of directly capturing the three-dimension information on forest structure via actively transmitting laser pulses that interact with forest structure and then receiving the return signals. It has evolved into the preeminent remotely sensed platform to characterize detailed information of forest attributes spatially, since the end of the last century [10][11][12][13][14][15][16][17][18] due to its high precision and flexibility critical for operational forest management, and it has been extensively adopted for artificial or natural forest attributes monitoring on the individual tree-level [19][20][21] and small-scale [22][23][24]. Moreover, forest volume, as one of the structure parameters, was often accurately estimated by LiDAR [25], for example, Clementel et al [26] have carried out statistical models combined with medium-resolution LiDAR to produce timber volume mapping, and Lo et al [19] demonstrated tree growth competition index (LCI) derived from LiDAR scanning while using a rasterized canopy height model (multilevel morphological active-contour algorithm) was a key factor for forest volume estimation.…”
Section: Introductionmentioning
confidence: 99%
“…Since the earliest remote sensing studies, pixel‐based image analysis has been the mainstay of automated image classification (Duro, Franklin, & Dubé, ), although more recently OBIA has become increasingly popular (Blaschke, ). Several studies have compared the two methods (Castillejo‐González et al, ; Cleve, Kelly, Kearns, & Moritz, ; Duro et al, ; Whiteside, Boggs, & Maier, ; Yu et al, ) and have frequently found OBIA to be more accurate (Xu, Morgenroth, & Manley, ); but this is not true in all cases (Duro et al, ). A UAV‐based IAP study (Mafanya et al, ) compared both methods and found that the accuracy of was similar.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Laser pulses can penetrate the canopy permitting the 3D imaging of the vertical strata of the vegetation. The study by Xu et al [29], which focuses on data provided by the 5 m-spatial resolution imagery of RapidEye and by aircraft-LiDAR in radiata pine stands, stands out in the field of LiDAR-based detection of very small, forested areas. A different approach was followed by Palenichka et al [30], who developed an algorithm for multi-scale segmentation of forested areas, from a stand level to an individual-tree level.…”
Section: Introductionmentioning
confidence: 99%